Shakespeare’s Literary Architecture in King Lear - Mike, Laura (Hungarian Journal of English and American Studies, 2022)
Book review:Mudriczki, Judit. Shakespeare’s Art of Poesy in King Lear: An Emblematic Mirror of Governance on the Jacobean Stage. Budapest–Párizs: L’Harmattan, 2020. 126 pages. ISBN 978-2-343-20808-4. Pbk. 1990 HUF.